Efeito dos processos de centrifugação, diluição e descongelação sobre a qualidade do sêmen de catetos (Tayassu tajacu, Linnaeus, 1758) - Castelo, Thibério de Souza (Universidade Federal Rural do Semi-Árido, 2010)
We evaluated the effect of centrifugation and the use of Tris-based extender supplemented with different sugars as well as different rates of thawing on the kinematic pattern of motility and other characteristics of frozen-thawed semen from captive collared peccaries. Semen from 13 collared were collected by electroejaculation and evaluated subjectively for motility, vigor and by computer analysis (CASA). Other features such as sperm viability, membrane integrity and morphology of spermatozoa were also evaluated. Semen was divided into four portions: two were subjected to centrifugation and then diluted in a tris plus fructose and the other in tris supplemented with glucose, the other two forms were immediately diluted in the same way. Egg yolk (20%) and glycerol (6%) were added to all groups. The samples were frozen in liquid nitrogen and thawed using two thawing rates (37ºC/1min and 55°C/7s). The results showed a reduction in total motility immediately after the dilution using both extenders and interference in some kinematic parameters such as BCF, LIN and STR for the samples centrifuged, , in addition, an increase in the number of total and secondary morphological defects were observed in centrifuged samples, independent to the sugar used (P <0.05). No significant differences among the extenders supplemented with fructose or glucose were verified at any time (P> 0.05). Furthermore, no interaction between the supplementation of sugar and thawing rates were observed for any semen parameter evaluated (P> 0.05). In conclusion, it is not necessary to centrifuge the semen from collared prior to the procedure of freezing and thawing, which can be achieved through a Tris-based extender supplemented with either fructose or glucose, as well as using different thawing rates (37ºC/1min and 55°C/7s).
Effect of the procedures for centrifugation, dilution and thawing on the quality of the semen of collared peccary (Tayassu tajacu, linnaes, 1758)
Keywords: Semen; Collared peccary (Tayassu tajacu); Cryopreservation; Centrifugation; Extenders; Sugars; Thawing rate; Sêmen cateto (Tayassu tajacu); Criopreservação; Centrifugação; Diluentes; Açúcares; Taxa de descongelação; CIENCIAS AGRARIAS::MEDICINA VETERINARIA